Involvement of Students in the Performance of Test Tasks and Conducting Control Work in the Lessons of Descriptive Geometry and Engineering Graphics (Journal of Architectural Design, 2022)
The article describes the existing problems and their solutions and theoretical foundations in the design and organization of test items for independent study of students in the field of "Descriptive Geometry and Engineering", the assessment of students with test items and the formation of knowledge, skills and abilities.